Entrepreneurship Development Based on Financial Management for the Community Kota Bambu Selatan - Palmerah, West Jakarta - Sumarto, Agus Herta; Soelton, Mochamad; Siswanti, Indra; Hanafiah, Ali; Thoullon, Muhammad Shirhan; Ali, Anees Jane; Karyatun, Subur (PT FORMOSA CENDEKIA GLOBAL, 2024)
The waste problem in Indonesia is no longer strange, recently the waste problem, which is becoming increasingly mounting day by day, has become a topic of conversation that has attracted the attention of every group. The problem of waste has become a daily problem for Indonesian people. Various types of waste have colored our every point of view. Waste is a serious matter that must be dealt with immediately. You can imagine the waste thrown away by households and industry. And like it or not, we have to admit that the Indonesian people still don't understand much about waste. Various methods have been taken by the government and some communities to reduce the volume of waste in Indonesia. Therefore, as an alternative way, I tried to use unused drink packaging cardboard into a unique wall decoration with high selling value. Carrying out community service activities regarding used goods waste is very challenging for our implementing team. Our activities include socializing the use of domestic waste, apart from being able to process it into craft innovations, to support the Urban MSME program RT 11/RW 06 Kota Bambu Selatan Subdistrict, Palmerah, West Jakarta and socializing the use of domestic waste to create waste from used goods. Later, residents, especially the Karang Taruna RT 11/RW 06, Kota Bambu Selatan Village, Palmerah, West Jakarta, can start creating creativity from used goods